A systematic literature review of mobility attitudes and mode choices: MENA and South Asian cities - Chaudhry, Abdul-Ghaffar; Masoumi, Houshmand; Dienel, Hans-Liudger (Frontiers in Sustainable Cities, 2023)
Urban mobility behavior is influenced by complex interrelations of personal attitudes, neighborhood design, emerging digitalized shared mobility services, and urban governance. The transformation of urban mobility ecosystems in the Middle East and North African (MENA) and the South Asian (SA) regions lacks an in-depth comparative review to understand the determinants of mobility attitudes and mode choices. The objective of this paper is to systematically study the existing literature on cities in the MENA and SA regions to provide a comparative review of the analyses and the findings on urban mobility attitudes in light of prevailing societal conditions and urban-spatial forms. A systematic methodology was deployed to shortlist recently published journal papers from the years 2000 to 2022 for the MENA and SA regions. Application of the (shortlisting) methodology has identified 43 studies from the MENA region and 43 papers from the SA region to be most suitable for the review of comparative analysis of urban mobility behavior. The review found that travel choices in both MENA and the SA regions are impacted by the usual determinants such as demography, socio-economic characteristics, vehicle ownership, and the quality and maturity of (urban transport) spatial forms. The mobility behavior in these regions, is to some extent, can be said to be in alignment with the observed behavior across the developed western cities elsewhere in Europe and North America. The review identified that in both the MENA and the SA regions, mobility choices are also influenced by certain additional factors, such as cultural norms, adverse climatic conditions and socio-economic standings, etc. The literature indicates that ethnic and income disparities are deeply embedded in the socio-spatial arrangements of the cities in the MENA and SA regions. Future research can assess the relative influence of these factors and to determine correlations between mobility attitudes and urban forms to build better cities.